Ordovician horseshoe crab body and trace fossil association preserved in a unique taphonomic setting - Russell D.C. Bicknell; Julien Kimmig; Carmela Cuomo; Aaron Goodman; Gregory D. Edgecombe; Benoit Issautier; Yannick Callec; Jan Freedman (Gondwana Research, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

A half-century of nuclear research, education and training: Story of the JSI TRIGA reactor - Luka Snoj; Klemen Ambrožič; Loïc Barbot; Ljudmila Benedik; Arne Bratkič; Ivana Capan; Christelle Reynard-Carette; Vladimir Cindro; Dušan Čalič; Christophe Destouches; Benoit Geslot; Alireza Haghighat; et al. (Annals of Nuclear Energy, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Impact of different weather generator scenarios on extreme flood estimates in Switzerland - Eleni Kritidou; Martina Kauzlaric; Maria Staudinger; Guillaume Evin; Benoit Hingray; Marc Vis; Jan Seibert; Daniel Viviroli (Stochastic Environmental Research and Risk Assessment, 2025)
The estimation of extreme floods using long continuous simulations is linked to uncertainties which are inherent in different components of the modeling chain. The main objective of this study was to investigate the role of precipitation input data from a weather generator for extreme flood estimates. A hydrometeorological modeling chain consisting of a multi-site weather generator (GWEX) at an hourly time scale, a rainfall-runoff model (HBV) and a hydrologic routing model (RS Minerve), was implemented, using different parameterizations of GWEX. While the sensitivity to the altered precipitation inputs was not uniform across the selected catchments due to their different physiographic characteristics, we found that the uncertainty of flood estimates increased with increasing return period. In addition, the flood peaks were strongly affected when a bootstrapping of precipitation was performed and to a lesser extent when weather types (WT) were used to condition the parameters of GWEX. However, the latter seemed to reduce the spread of the uncertainty both in generated precipitation and simulated floods. Therefore, results suggested that precipitation inputs strongly contribute to the uncertainties of extreme floods. Accounting for uncertainty information enhances the usefulness of long continuous simulations and is essential as a context for applications including hydraulic engineering, spatial planning and safety assessments.

Nanostructure and interfacial mechanical properties of PEG/cellulose nanocomposites studied with molecular dynamics - Wenqiang Liu; Ali Shomali; Chi Zhang; Benoit Coasne; Jan Carmeliet; Dominique Derome (Carbohydrate Polymers, 2024)

Assessment of receptor-mediated activity (AhR and ERα), mutagenicity, and teratogenicity of metal shredder wastes in Wallonia, Belgium - Besarta Matranxhi; Birgit Mertens; Roel Anthonissen; Jan Maes; Annelii Ny; Peter de Witte; Jean-Marc Brouhon; Benoit De Bast; Marc Elskens (Environmental Science and Pollution Research, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Regional invasion history and land use shape the prevalence of non‐native species in local assemblages - Daijun Liu; Franz Essl; Bernd Lenzner; Dietmar Moser; Philipp Semenchuk; Tim M. Blackburn; Phillip Cassey; Dino Biancolini; César Capinha; Wayne Dawson; Ellie E. Dyer; Benoit Guénard; et al. (Global Change Biology, 2024)
The ecological impact of non‐native species arises from their establishment in local assemblages. However, the rates of non‐native spread in new regions and their determinants have not been comprehensively studied. Here, we combined global databases documenting the occurrence of non‐native species and residence of non‐native birds, mammals, and vascular plants at regional and local scales to describe how the likelihood of non‐native occurrence and their proportion in local assemblages relate with their residence time and levels of human usage in different ecosystems. Our findings reveal that local non‐native occurrence generally increases with residence time. Colonization is most rapid in croplands and urban areas, while it is slower and variable in natural or semi‐natural ecosystems. Notably, non‐native occurrence continues to rise even 200 years after introduction, especially for birds and vascular plants, and in other land‐use types rather than croplands and urban areas. The impact of residence time on non‐native proportions is significant only for mammals. We conclude that the continental exchange of biotas requires considerable time for effects to manifest at the local scale across taxa and land‐use types. The unpredictability of future impacts, implied by the slow spread of non‐native species, strengthens the call for stronger regulations on the exchange of non‐native species to reduce the long‐lasting invasion debt looming on ecosystems' future.

Improved large-area forest increment information in Europe through harmonisation of National Forest Inventories - Thomas Gschwantner; Thomas Riedel; Lea Henning; Patricia Adame; Radim Adolt; Ana Aguirre; Iciar Alberdi; Valerio Avitabile; Isabel Cañellas; Lucio Di Cosmo; Christoph Fischer; Alexandra Freudenschuß; et al. (Forest Ecology and Management, 2024)

DNA metabarcoding reveals a diverse, omnivorous diet of Arctic amphipods during the polar night, with jellyfish and fish as major prey - Annkathrin Dischereit; Jan Beermann; Benoit Lebreton; Owen S. Wangensteen; Stefan Neuhaus; Charlotte Havermans (Frontiers in Marine Science, 2024)
Introduction Currently, Arctic marine ecosystems are witnessing the most rapid physical changes worldwide, leading to shifts in pelagic and benthic communities and food web structure, concomitant with the introduction of boreal species. Gelatinous zooplankton or jellyfish represent one particular group of which several boreal species are prone to undergo significant poleward range expansions and population increases in the Arctic in the course of the ongoing changes. Historically, jellyfish were considered a trophic dead-end, but an increasing number of studies using modern tools have highlighted their role as major prey items in marine food webs. In this study, we aimed to verify the role of jellyfish and other metazoans as food sources in the Arctic polar night food web, when pelagic resources are limited. Methods We identified the diet of different bentho-pelagic amphipod species in the Atlantifying Kongsfjorden (West Svalbard) during the polar night. We regularly sampled lysianassoid and gammarid amphipods using baited traps and hand nets over a period of one month during the polar night and identified their diet spectrum by applying DNA metabarcoding (COI) to their stomach contents. Results We demonstrate that all investigated species are omnivorous. Fish species including polar cod and snailfish, likely in the shape of carrion, played an important role in the diet of the scavengers Orchomenella minuta and Anonyx sarsi . Predation and potential scavenging on jellyfish contributed to the diet of all four investigated species, particularly for the species Gammarus setosus and G. oceanicus , as evidenced by high read abundances and high frequencies of occurrence. Besides jellyfish, crustaceans and macroalgae were important components of the diet of the two Gammarus species. Discussion The diverse jellyfish community present in Kongsfjorden in the polar night is clearly being utilized as a food source, either through pelagic feeding or feeding on jelly-falls, albeit to a different extent in the local amphipod community. These findings provide novel insights into the Arctic food web during the polar night and represent the first evidence of feeding on natural (non-experimental) jelly-falls.

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Impact of concomitant acid suppressive therapy on pazopanib efficacy and dose reductions in patients with metastatic renal cell carcinoma - Greet Van De Sijpe; Benoit Beuselinck; Tine Van Nieuwenhuyse; Roxanne Poncelet; Oliver Bechter; Maarten Albersen; Eduard Roussel; Marcella Baldewijns; Jan Tack; Isabel Spriet (European Journal of Clinical Pharmacology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Globally Consistent Quantitative Observations of Planktonic Ecosystems - Fabien Lombard; Emmanuel Boss; Anya M. Waite; Meike Vogt; Julia Uitz; Lars Stemmann; Heidi M. Sosik; Jan Schulz; Jean-Baptiste Romagnan; Marc Picheral; Jay Pearlman; Mark D. Ohman; et al. (Frontiers in Marine Science, 2019)

Development and implementation of eco-genomic tools for aquatic ecosystem biomonitoring: the SYNAQUA French-Swiss program - Estelle Lefrançois; Laure Apothéloz-Perret-Gentil; Philippe Blancher; Samuel Botreau; Cécile Chardon; Laura Crepin; Tristan Cordier; Arielle Cordonier; Isabelle Domaizon; Benoit J. D. Ferrari; Julie Guéguen; Jean-Christophe Hustache; et al. (Environmental Science and Pollution Research, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Erratum to: Western US high June 2015 temperatures and their relation to global warming and soil moisture - Sjoukje Y. Philip; Sarah F. Kew; Mathias Hauser; Benoit P. Guillod; Adriaan J. Teuling; Kirien Whan; Peter Uhe; Geert Jan van Oldenborgh (Climate Dynamics, 2018)

Western US high June 2015 temperatures and their relation to global warming and soil moisture - Sjoukje Y. Philip; Sarah F. Kew; Mathias Hauser; Benoit P. Guillod; Adriaan J. Teuling; Kirien Whan; Peter Uhe; Geert Jan van Oldenborgh (Climate Dynamics, 2018)

Comparative analysis of spatial genetic structure in an ant–plant symbiosis reveals a tension zone and highlights speciation processes in tropical Africa - Rumsaïs Blatrix; Jean Peccoud; Céline Born; Finn Piatscheck; Laure Benoit; Mathieu Sauve; Champlain Djiéto‐Lordon; Christiane Atteke; Jan J. Wieringa; David J. Harris; Doyle McKey (Journal of Biogeography, 2017)
Aim Pleistocene climatic oscillations induced range fluctuations in African rain forest organisms and may have shaped species diversification through allopatric speciation events. We compared the spatial genetic structure of two forest species that live in obligate symbiosis and thus must have experienced the same range fluctuations, as a means to discriminate incipient speciation from transient differentiation simply resulting from past divergence. Location Western central Africa. Methods We genotyped 765 individuals of the tree Barteria fistulosa and 605 colonies of its symbiotic ant Tetraponera aethiops at 12 and 13 microsatellite loci, respectively. We compared the spatial genetic structure of the two symbionts by using Bayesian clustering algorithms, isolation‐by‐distance analyses and clines of synthetic alleles. We used species niche modelling (climatic and soil variables) to investigate ecological variables associated with genetic discontinuities in tree populations. Results The trees and the ants showed congruent patterns of spatial genetic structure. However, the trees showed a very steep genetic discontinuity between groups north and south of latitude 1° N, which was much weaker in the ants. There was no evidence for effective gene flow between the two tree lineages in contact at the transition zone, despite the presence of a few hybrids. Niche modelling did not predict the occurrence of northern trees south of this genetic transition, and vice versa. Main conclusions The genetic discontinuity near latitude 1° N is inferred to be a tension zone resulting from reproductive incompatibilities between previously allopatric tree lineages. This tension zone may have stabilized at a climatic transition (between boreal and austral seasonal regimes), and matches patterns of genetic structure previously observed in other forest plant species. Our results illustrate independent speciation between two species that live in specific and obligate symbiosis and suggest that a tension zone may separate lineages of several central African forest plants near the thermal equator.

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Impacts of Coastal Acidification on the Pacific Northwest Shellfish Industry and Adaptation Strategies Implemented in Response - Alan Barton; George Waldbusser; Richard Feely; Stephen Weisberg; Jan Newton; Burke Hales; Sue Cudd; Benoit Eudeline; Chris Langdon; Ian Jefferds; Teri King; Andy Suhrbier; et al. (Oceanography, 2015)

B acillus subtilis attachment to A spergillus niger hyphae results in mutually altered metabolism - Isabelle Benoit; Marielle H. van den Esker; Aleksandrina Patyshakuliyeva; Derek J. Mattern; Felix Blei; Miaomiao Zhou; Jan Dijksterhuis; Axel A. Brakhage; Oscar P. Kuipers; Ronald P. de Vries; Ákos T. Kovács (Environmental Microbiology, 2015)
Summary Interaction between microbes affects the growth, metabolism and differentiation of members of the microbial community. While direct and indirect competition, like antagonism and nutrient consumption have a negative effect on the interacting members of the population, microbes have also evolved in nature not only to fight, but in some cases to adapt to or support each other, while increasing the fitness of the community. The presence of bacteria and fungi in soil results in various interactions including mutualism. Bacilli attach to the plant root and form complex communities in the rhizosphere. B acillus subtilis , when grown in the presence of A spergillus niger , interacts similarly with the fungus, by attaching and growing on the hyphae. Based on data obtained in a dual transcriptome experiment, we suggest that both fungi and bacteria alter their metabolism during this interaction. Interestingly, the transcription of genes related to the antifungal and putative antibacterial defence mechanism of B . subtilis and A . niger , respectively, are decreased upon attachment of bacteria to the mycelia. Analysis of the culture supernatant suggests that surfactin production by B . subtilis was reduced when the bacterium was co‐cultivated with the fungus. Our experiments provide new insights into the interaction between a bacterium and a fungus.

Extreme plasticity in life‐history strategy allows a migratory predator (jumbo squid) to cope with a changing climate - Henk‐Jan T. Hoving; William F. Gilly; Unai Markaida; Kelly J. Benoit‐Bird; Zachary W. ‐Brown; Patrick Daniel; John C. Field; Liz Parassenti; Bilin Liu; Bernardita Campos (Global Change Biology, 2013)
Dosidicus gigas (jumbo or Humboldt squid) is a semelparous, major predator of the eastern Pacific that is ecologically and commercially important. In the Gulf of California, these animals mature at large size (>55 cm mantle length) in 1–1.5 years and have supported a major commercial fishery in the Guaymas Basin during the last 20 years. An El Niño event in 2009–2010, was accompanied by a collapse of this fishery, and squid in the region showed major changes in the distribution and life‐history strategy. Large squid abandoned seasonal coastal‐shelf habitats in 2010 and instead were found in the Salsipuedes Basin to the north, an area buffered from the effects of El Niño by tidal upwelling and a well‐mixed water column. The commercial fishery also relocated to this region. Although large squid were not found in the Guaymas Basin from 2010 to 2012, small squid were abundant and matured at an unusually small mantle‐length ( D. gigas to rapidly adapt to and cope with El Niño. This ability is likely to be an important factor in conjunction with longerterm climate‐change and the potential ecological impacts of this invasive predator on marine ecosystems.

Carbon, nitrogen and Greenhouse gases budgets over a four years crop rotation in northern France - Benjamin Loubet; Patricia Laville; Simon Lehuger; Eric Larmanou; Christophe Fléchard; Nicolas Mascher; Sophie Genermont; Romain Roche; Rossana M. Ferrara; Patrick Stella; Erwan Personne; Brigitte Durand; et al. (Plant and Soil, 2011)

Pelagic food web patterns: do they modulate virus and nanoflagellate effects on picoplankton during the phytoplankton spring bloom? - Pascaline Ory; Hans J. Hartmann; Florence Jude; Christine Dupuy; Yolanda Del Amo; Philippe Catala; Françoise Mornet; Valérie Huet; Benoit Jan; Dorothée Vincent; Benoit Sautour; Hélène Montanié (Environmental Microbiology, 2010)
Summary As agents of mortality, viruses and nanoflagellates impact on picoplankton populations. We examined the differences in interactions between these compartments in two French Atlantic bays. Microbes, considered here as central actors of the planktonic food web, were first monitored seasonally in Arcachon (2005) and Marennes‐Oléron (2006) bays. Their dynamics were evaluated to categorize trophic periods using the models of Legendre and Rassoulzadegan as a reference framework. Microbial interactions were then compared through 48 h batch culture experiments performed during the phytoplankton spring bloom, identified as herbivorous in Marennes and multivorous in Arcachon. Marennes was spatially homogeneous compared with Arcachon. The former was potentially more productive, featuring a large number of heterotrophic pathways, while autotrophic mechanisms dominated in Arcachon. A link was found between viruses and phytoplankton in Marennes, suggesting a role of virus in the regulation of autotroph biomass. Moreover, the virus–bacteria relation was weaker in Marennes, with a bacterial lysis potential of 2.6% compared with 39% in Arcachon. The batch experiments (based on size‐fractionation and viral enrichment) revealed different microbial interactions that corresponded to the spring‐bloom trophic interactions in each bay. In Arcachon, where there is a multivorous web, flagellate predation and viral lysis acted in an opposite way on picophytoplankton. When together they both reduced viral production. Conversely, in Marennes (herbivorous web), flagellates and viruses together increased viral production. Differences in the composition of the bacterial community composition explained the combined flagellate‐virus effects on viral production in the two bays.

Biotechnological applications and potential of fungal feruloyl esterases based on prevalence, classification and biochemical diversity - Isabelle Benoit; Etienne G. J. Danchin; Robert-Jan Bleichrodt; Ronald P. de Vries (Biotechnology Letters, 2008)

Energy, transport and waste models - Jan Braam; Toini M. Tanner; Cecilia Askham; Nicoline Hendriks; Benoit Maurice; Helena Mälkki; Mie Vold; Helena Wessman; Angeline S. H. de Beaufort (The International Journal of Life Cycle Assessment, 2001)

On the limits of applicability of spectrophotometric and spectrofluorimetric methods for the determination of chlorophyll a/b ratio - Roman Kouril; Petr Ilík; Jan Naus; Benoit Schoefs (Photosynthesis Research, 1999)